The presence of Mak Andam in the Lingga Malay Traditional Cultural Wedding Procession - Hendra, Doni Febri (Universitas Negeri Medan, 2023)
This study aims to determine the role of Mak Andam in traditional Malay Lingga marriage using a qualitative approach. Mak Andam plays an important role in preparing brides-to-be, and its role in organizing Malay wedding ceremonies has a rich cultural and social dimension. Qualitative research methods are used to understand more deeply about Mak Andam's role, their perceptions, experiences, and perspectives on Malay marriage. This study used in-depth interviews with Mak Andam who is experienced in engaging in Malay marriages. The qualitative data obtained from the interviews were analyzed using content analysis to identify key themes related to Mak Andam's role. Research findings suggest that Mak Andam's role in Malay Lingga weddings includes a wide range of duties, from dressing the bride and groom to providing emotional support. Mak Andam also has in-depth knowledge of Malay wedding traditions and plays an important role in maintaining the authenticity and sustainability of this cultural heritage. They also have a great influence in creating meaningful experiences for the bride. This research provides a deeper understanding of Mak Andam's existence in Lingga Malay marriages, by explaining the complexity of their social and cultural roles. These findings contribute to the preservation and further understanding of traditional Malay wedding culture and may also be useful in the context of the preservation of similar cultures and customs around the world.